Влияние деформационной обработки на механическое поведение сплава АМг5-AI3Er - Ахмадиева, Анастасия Алексеевна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
This article investigates the effect of deformation processing on the mechanical behavior of the AA5056 alloy with the addition of erbium. Due to the difference in melting temperatures, erbium was introduced into the aluminum melt as part of the master alloy obtained by shock-wave compaction. According to the results of uniaxial tension at room temperature, a positive effect of rolling on the strength properties of the AA5056+AlsEr alloy was noted.